O Araçá amarelo...: estudo sobre a participação dos usuários no controle público da política de assistência social no município de São Paulo: limites, desafios e possibilidades 2002-2012 - Ferreira, Deocleciana (2013)
The purpose of this dissertation was to analyze the participation of users in public control of Social Assistance Policy in São Paulo city mainly in the deliberative dynamic of the Council considering the period from 2002 to 2012. The aim of the research was to analyze its limits, challenges and possibilities with the purpose of evaluating the performance of COMASP/SP related to political, technical and operational aspects. The study aimed to know the version of the persons involved in the study about periods and facts related to Brazilian Social Protection from a transversal look to public control and defense of citizenship. It is a qualitative research based on methodological trajectories. It was supported on tales in order to emphasize an approach to the characters feelings with autobiographic roots. The basic concepts adopted are: Public Control, Citizenship and Social subjects, based on contemporaneous authors, mainly Brazilian, with bibliographic survey in the fields of Sociology, Social Sciences and Phylosophy, documental research in personal files of the people involved in the research, Instituto Polis, PUC-SP- Nadir Kfouri Library, ESPASO, Council site, Municipality departments, etc. The field research consisted of open interviews in which where listened the narratives of five citizens, tree of them had been Social Assistance Councillors. Their life stories were woven in fighting for life in some moments in the past. They are two activists of social fóruns, a actual member of CNAS from 2012 to 2014 and the other is a member of the coordination of National Movement of Homeless.To the data analysis were applied documental and analysis techniques and content analysis of the narrated stories. The results found in the investigation have shown in the one hand , mainly the activity participation in deliberative of COMAS, due to the fact they were chosen by the users and on the other hand the weakness as a result of the established bureaucratic and institutional order that favors the technical aspect, thus highlighting the limitations of the political role to play of the Council.That is why we emphasize the importance of the debate on overcoming the social issue by the public control as power sharing and expansion of the state. It was sought to support the new knowledge by creating proposals attempting to smooth out the rough edges in the historical formulating of social protection and strengthening spaces for democratic participation as a result of the subjects experiences with an unique approach with actions in defense of the citizenship